From research into practice: converting epidemiological data into relevant information for planning of regional health services for refugees in germany - Hintermeier, Maren; Gold, Andreas W.; Erdmann, Stella; Perplies, Clara; Bozorgmehr, Kayvan; Biddle, Louise (International journal of environmental research and public health, 2022)
Health data of refugees and asylum seekers (ASR) is not routinely collected in Germany. Based on health data of ASR collected in 2018 in regional accommodation centres, we developed a dashboard to estimate regional burden of disease in Baden-Wuerttemberg, Germany. We aimed to find out how scientific data can support actors involved in healthcare planning for ASR in Germany and, within this scope, to explore how healthcare planning is conducted in this context. We conducted 12 qualitative semi-structured interviews including a usability test for a health data dashboard with regional decision-makers. Results showed that healthcare planning processes for ASR in Germany involve a complex set of actors in both long- and short-term decision-making. Data gained from representative surveys can support long-term decision-making and thus support the resilience of the health system, but it must balance the need for simple data presentation with transparent communication of potentially complex methods.
Gesehen am 06.09.2022